Differential scanning calorimetric analysis of palm oil, palm oil based products and coconut oil: effects of scanning rate variation - Tan, C.P; Che Man, Y.B (Elsevier, 2002)
This study explored the thermal behaviour of coconut oil and palm oil and products based on them, by monitoring peak transition temperatures, transition enthalpies, offset- (Toff) and onset-temperatures (Ton) by differential scanning calorimetry (DSC) at different scanning rates. Triacylglycerol (TAG) profiles and iodine value (IV) analyses were used to compliment the DSC data. An increase in heating rate, generally, was associated with an increase in peak size, peak transition and offset temperatures. Meanwhile, the peak transition and onset temperatures increased with decreasing cooling rates. Decreased heating or cooling rate also caused a narrowing of the melting endotherms or crystallisation exotherms. Transitions for oil samples with low scanning rate (1 °C/min) were composed of more peaks, resulting from the contribution of a number of TAG components in the oil. Generally, coconut oils and palm-based products may be differentiated with their Toff and Ton values in the DSC melting and crystallisation curves, respectively. On the basis of the results of this study, DSC can provide information about the nature of TAG interaction in these oil samples. Recognition of the pattern of interactions among TAG in coconut- and palm-based products can be helpful in many physical processes in the palm oil industry.